Work-Family Conflict, Readiness for Change and Employee Performance Relationship During the Covid-19 Pandemic - Masduki Asbari; Dewiana Novitasari; Erni Taruli Pebrina; Joko Santoso (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2020)
This study aimed to measure the effect of work-family conflict on employee performance of the part-time employee of a packaging industry in Tangerang which are mediated by readiness for change. Data collection was done by simple random sampling technique and the returned and valid questionnaire results were 143 participants. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that work-family conflict have negative and significant effect on the employee performance, but work-family conflict have a positive and significant effect on readiness for change. Also, this research found that readiness for change have a positive and significant effect on relationship work-family conflict and employee performance. Readiness for change as fully mediator. This new research proposed a model for building employee performance among the part-time employee of a packaging industry in Tangerang through enhancing work-family conflict management practice with readiness for change as a mediator. This research could pave the way to improve employee readiness in facing the era of industrial revolution 4.0. Keywords: Employee Performance, Readiness for Change, Work-Family Conflict